Pengaruh Model Pembelajaran Project Based Learning Terhadap Pemahaman Konsep IPA Siswa Sekolah Dasar - Aryani, Eka; Ariefka, Reza (LPPPI Publishing, 2025)
This study aims to determine the significant effect of using the Project Based Learning learning model on students' understanding of science concepts in elementary schools. The research method used is an experiment (quasi-experiment) with a non-equivalent control group design. The population in this study were all fourth-grade students of SDN 5 Kampung Baru. The research sample used was 50 students, namely 25 students of class IV A and 25 of class IV B. The data collection technique used was a multiple-choice test. The results of this study were obtained through the Independent Sample T-test or hypothesis test with a significance value of <,001. Based on the results of these values, it can be concluded that the probability of significance <0.05 so that H_a is accepted and H_o is rejected. From these results, it can be concluded that the project-based learning model has an effect on the understanding of science concepts of fourth-grade students at SDN 5 Kampung Baru.